Uvulopalatopharyngoplasty with or without tonsillectomy in the treatment of adult obstructive sleep apnea: a systematic review - Stuck, Boris; Ravesloot, Madeline J. L.; Eschenhagen, Till; De Vet, H. C. W.; Sommer, Ulrich (Sleep medicine, 2018)
Background - The most commonly performed surgical procedure for obstructive sleep apnea (OSA) is uvulopalatopharyngoplasty with or without tonsillectomy (UPPP ± TE). However, there is currently no review solely focusing on clinically relevant effects of standard UPPP technique with or without tonsillectomy as a monotherapy in patients with OSA. - Methods - A systematic review and meta-analysis were performed to assess the effects of isolated UPPP ± TE in patients with OSA. Studies of any design referring to adult patients with obstructive sleep apnea diagnosed via polysomnography or comparable objective measures were considered, in which isolated “standard” UPPP ± TE was performed. - Results - Forty-eight studies were included for the qualitative analysis. All but one study demonstrated a reduction in the frequency of respiratory events and success/response rates ranged from 35 to 95.2%. In the six studies that reported pre- and postoperative mean scores of the Epworth Sleepiness Scale (ESS), a reduction in sleepiness scores was demonstrated. Data addressing the effect of UPPP ± TE in comparison to no treatment or control were available from two randomized controlled trials (RCT). When pooling the data, UPPP ± TE was significantly more effective in reducing the apnea-hypopnea index (AHI) and Epworth Sleepiness Scale (ESS) (large effect): an AHI mean difference (MD) of −18.59 (95% CI −34.14, −3.04) and an ESS MD of −5.37 (95% CI −7,03, −3.72). Data addressing effect of UPPP ± TE in comparison to baseline was available from three RCT. When pooling the data, the AHI was reduced from a mean 35.4 to 17.9 (49.5% reduction); a MD of −20.41, 95% CI −32.78, −8.04 (−1.80, −1.15) (large effect). Various additional beneficial effects of UPPP ± TE were demonstrated including improvement in sexual function, ventricular function, sleep stages, serum lipid, depressive disorder and driving performance. - Conclusion - UPPP ± TE reduces respiratory events and daytime sleepiness in adult patients with OSA and UPPP ± TE is superior to non-treated controls in this regard. Further research is needed to establish the long-term benefit, the impact on cardiovascular morbidity and the role of UPPP ± TE in the variety of available treatment options for OSA.
Gesehen am 23.04.2019